2019
DOI: 10.21276/ijcmr.2019.6.8.56
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Deaths due to Railway Accidents Reported at a Tertiary Care Hospital Mortuary during the Period of January to December 2015

Abstract: Introduction: Cities are locations having a high level of accumulation and concentration of economic activities and are complex spatial structures that are supported by transport systems. The evolution of mass rapid transport system in the form of suburban railway network has increased railway casualties in the cities as the railroads pass through residential and commercial zones. Hence, the aim of the present study was to assess the analysis of death due to railway accidents in a tertiary care hospital. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In the present Study Male were the Major number of Victims[n-24/32], forming 7:1 Ratio, similar were the observations made by Moses et al, 7 wherein the Victims Sex Ratio was 6.5:1. The results are close to similar studies conducted by Ibrahim et al 5 and Radbo H. 8 The Majority of the Victims[n-26] were Identified Bodies in the Present Cases, however 19%[n-06] were Unidentified at the time of recovery of the mutilated remains.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present Study Male were the Major number of Victims[n-24/32], forming 7:1 Ratio, similar were the observations made by Moses et al, 7 wherein the Victims Sex Ratio was 6.5:1. The results are close to similar studies conducted by Ibrahim et al 5 and Radbo H. 8 The Majority of the Victims[n-26] were Identified Bodies in the Present Cases, however 19%[n-06] were Unidentified at the time of recovery of the mutilated remains.…”
Section: Resultssupporting
confidence: 91%
“…In the present Study 75% [n-24] of the victims were suicidee and only 19% [n-6] of Victims died due to Accident and only 6.25%[n-02] were due to Homicides. This is in Contrast to Study Conducted by Ibhraim Jebril, 5 Valsala K. et al, 4 Moses et al, 7 wherein their observations indicated Accidents as the common Mode of Death in 91.5, 62.5% & 63% of Accident Respectively. This Wide Variations is due to the Regional, Urban Factors, as it is widely known that Suicides are more common in Urban and Industrial Regions than in Rural Regions.…”
Section: Resultsmentioning
confidence: 58%
“…Most of the railway related deaths happen to be accidental in nature (63.83%) although suicidal deaths are not uncommon (35.11%) and in 1 occasion, a case of homicide with post mortem railway injury was detected. Our observation is almost similar to the observation of other authors like S.J.Cina., 1 (92%), G.G.Davis., 2 (74.41%), M.K.Mohanty., 3 (80.7%), P.Ravi Kumar., 4 (72.12%), T. Mohit Kumar Moses., 5 (63%), B.Patil., 6…”
Section: Discussionmentioning
confidence: 99%